Domestic Spaces and Ecofeminism: Initiative «Ollita Común» in Young town Nuevo Perú in San Juan de Lurigancho - Gonzales Hilares, Jakeline (2024)
Because of the pandemic, in the young town of Nuevo Perú, domestic spaces extended beyond the physical territory of the home, in an initiative that the local inhabitants called Ollita Común Nuevo Perú. Through interviews and life stories collected in focus groups, the intervention of women in this experience is analyzed applying a gender perspective. The women’s initiative was not limited to cooking, since providing food implied facing care problems that required interventions not only in communal spaces, but also in public spaces. Likewise, the experience represents an example of care and preservation of the environment in the city.